2002
DOI: 10.1074/jbc.m108545200
|View full text |Cite|
|
Sign up to set email alerts
|

Kunitz-type Protease Inhibitor Bikunin Disrupts Phorbol Ester-induced Oligomerization of CD44 Variant Isoforms Containing Epitope v9 and Subsequently Suppresses Expression of Urokinase-type Plasminogen Activator in Human Chondrosarcoma Cells

Abstract: We previously found that bikunin (bik), a Kunitz-type protease inhibitor, suppresses phorbol ester (PMA)-stimulated expression of urokinase-type plasminogen activator (uPA). In the present study, we tried to answer this mechanism using human chondrosarcoma HCS-2/8 cells. Our results showed the following novel findings: (a) the standard form of CD44 (CD44s; 85 kDa) is expressed in both unstimulated and PMA-stimulated cells, while CD44v isoforms containing epitope v9 (110 kDa) are strongly up-regulated in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Northern Blot Hybridization with cDNA Probes-Northern blot hybridization was carried out as described previously (19,20). Samples of total RNA (10 g) were separated by electrophoresis through denaturing 1.2% agarose gels containing 1% formaldehyde and transferred onto nylon or nitrocellulose membranes using standard molecular biological techniques.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Northern Blot Hybridization with cDNA Probes-Northern blot hybridization was carried out as described previously (19,20). Samples of total RNA (10 g) were separated by electrophoresis through denaturing 1.2% agarose gels containing 1% formaldehyde and transferred onto nylon or nitrocellulose membranes using standard molecular biological techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Samples of total RNA (10 g) were separated by electrophoresis through denaturing 1.2% agarose gels containing 1% formaldehyde and transferred onto nylon or nitrocellulose membranes using standard molecular biological techniques. Hybridization was carried out with [␣-32 P]dCTP by random oligonucleotide priming to specific activities of 0.4 -0.9 ϫ 10 9 cpm/ g. uPA cDNA was prepared as described (19,20). Filters were reprobed with the cDNA for glyceraldehyde-3-phosphate dehydrogenase to correct for the amount of RNA loaded onto the filters (19,20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene is also found to be selectively overexpressed in acute myelocytic leukemia [32]. The serine protease inhibitor, Kuniz type 2 [33], and the protein tyrosine phosphase, receptor type, F [34], take part in distinct cellular processes. The relevance of the up-regulation of these proteins is yet to be determined.…”
Section: Differential Expressions Of Genes In Bt-549 and Mda-mb-468 Cmentioning
confidence: 99%
“…One study has shown that certain recombinant forms of bikunin can have an inhibitory effect on HIV-1 infectivity in vitro (42). In cancers, its expression by human glioblastoma cells can cause suppression of tumor invasion (43), whereas addition of bikunin to human chondrosarcoma cell cultures blocks cell spreading (44).…”
Section: Table II N-terminal Sequences Of M-bik and M-ptgf-␤mentioning
confidence: 99%